Jews, Judaism, and the Reformation in sixteenth-century Germany - Bell, Dean Phillip; Burnett, Stephen G. (Brill, 2016)
This volume brings together important research on: the reception and representation of Jews and Judaism in late medieval German thought, the works of major Reformation-era theologians, scholars, and movements, and in popular literature and the visual arts; it also explores social, intellectual, and cultural developments within Judaism and Jewish responses to the Reformation in sixteenth-century Germany.